Prematurely aging mitochondrial DNA mutator mice display subchondral osteopenia and chondrocyte hypertrophy without further osteoarthritis features - Geurts, Jeroen (Sci Rep, 2020)
Mitochondrial mutations and dysfunction have been demonstrated in several age-related disorders including osteoarthritis, yet its relative contribution to pathogenesis remains unknown. Here we evaluated whether premature aging caused by accumulation of mitochondrial DNA mutations in Polg(D275A) mice predisposes to the development of knee osteoarthritis. Compared with wild type animals, homozygous Polg(D275A) mice displayed a specific bone phenotype characterized by osteopenia of epiphyseal trabecular bone and subchondral cortical plate. Trabecular thickness was significantly associated with osteocyte apoptosis rates and osteoclasts numbers were increased in subchondral bone tissues. While chondrocyte apoptosis rates in articular and growth plate cartilage were similar between groups, homozygous mitochondrial DNA mutator mice displayed elevated numbers of hypertrophic chondrocytes in articular calcified cartilage. Low grade cartilage degeneration, predominantly loss of proteoglycans, was present in all genotypes and the development of osteoarthritis features was not found accelerated in premature aging. Somatically acquired mitochondrial DNA mutations predispose to elevated subchondral bone turnover and hypertrophy in calcified cartilage, yet additional mechanical or metabolic stimuli would seem required for induction and accelerated progression of aging-associated osteoarthritis.